Similarity or Variation? Employee Representation and Consultation Approaches amongst Liberal Market Economy Multinationals - McDonnell, A.; Boyle, B.; Bartram, T.; Stanton, P.; Burgess, John (Universite Laval * Department of Industrial Relations, 2015)
This paper engages with the varieties of capitalism literature to investigate the employee representation and consultation approaches of liberal market economy multinational companies (MNCs), specifically Australian, British and US MNCs operating in Australia. The paper considers whether evidence points to similarity or variation amongst liberal market headquartered MNCs. Drawing on survey data of MNCs in Australia, the results show that UK-owned MNCs were the least likely to report collective structures of employee representation. It was found that Australian MNCs were the most likely to engage in collective forms of employee representation and made less use of direct consultative mechanisms relative to their British and US counterparts. Australian MNCs appear to have upheld long-standing national institutional arrangements to engage employees on a collective basis.